Differential modulation of the expression of important drug metabolising enzymes and transporters by endothelin-1 receptor antagonists ambrisentan and bosentan in vitro - Weiß, Johanna; Herzog, Melanie; Haefeli, Walter E. (European journal of pharmacology, 2011)
The safety and effectiveness of drugs used to treat chronic diseases critically depend on their propensity to interact with co-administered drugs. Induction of enzymes and drug transporters involved in the clearance and distribution of drugs may critically reduce exposure with their substrates and thus lead to nonresponse. We therefore investigated the impact of the endothelin-1 receptor antagonists bosentan and ambrisentan on the expression of relevant human efflux and uptake transporters and on phase 1 and phase 2 enzymes. LS180 adenocarcinoma cells were treated for four days with bosentan or ambrisentan (1-50μM), the positive control rifampicin, or medium only (negative control). For evaluation of bosentan also HuH-7 human hepatoma cells were used and treated similarly. Gene expression was quantified at the mRNA level by real-time reverse transcription polymerase chain reaction and for some genes also at the protein level by western blot analysis. Comparable to rifampicin, bosentan was a moderate to strong inductor for all cytochrome P450 isozymes and ATP-binding cassette transporters tested, and it also induced organic anion transporting polypeptides. 50μM bosentan up-regulated e.g. CYP3A4 8.5-fold, ABCB1 5.1-fold, and ABCB11 1.9-fold at the mRNA level in LS180 cells. In HuH-7 cells induction was much less pronounced (e.g. CYP3A4 1.9-fold for bosentan). In contrast, ambrisentan only weakly induced some of the genes investigated in LS180 cells. These findings corroborate the in vivo finding that bosentan is much more prone to drug interactions than ambrisentan.
Gesehen am 18.11.2022